ANALISIS SISTEM PELAYANAN GARDU TOL OTOMATIS GERBANG TOL GAYAMSARI MENGGUNAKAN METODE BAYESIAN - Akbari, Windusiwi Asih; Sugito, Sugito; Suparti, Suparti (Jurnal Gaussian, 2023)
Transportation is important things to support mobility. The high level of mobility is in line with the growth of vehicles which has increased causing congestion on roads. Highways are one of the government’s efforts to reduce congestion. Gayamsari Toll Gate is one of the toll gates in Semarang City that experiencing the phenomenon of queuing when paying tolls. This study aims to determine the operation of the service system by obtaining a queuing model and system performance measures from the distribution of arrivals and services. Bayesian method is used to determine the distribution of arrivals and services by finding the posterior distribution. The combination of the sample likelihood function and the prior distribution is known as Bayesian method. The prior distribution used is the previous research data which produces a negative binomial distribution. The likelihood function of the arrival sample in this study is discrete uniform and the likelihood function of the service sample produces a negative binomial distribution. The results are the queuing system model is (Beta/Beta/5): (GD/∞/∞). Based on the results of the queue simulation, we can assume that the service system is optimal.